Evaluasi Pendidikan Berbasis Al-Qur’an Sebuah Implementasi Pembelajaran Pai Di Smp Hang Nadim Malay School Kota Batam - Zainal Mutaqin (Journal on Education, 2023)
Since its inception, the Qur'an has given serious attention to the issue of educational evaluation using various terms such as; al-Mas'ul, al-Ihsha', al-'Adad, al-Bala', al-fitnah. The aim of the research is to describe the implementation of educational evaluation at the junior high school level. The research uses a case study research method. Data collection by interviews. Data analysis was carried out descriptively qualitatively. The research results show that the implementation of educational evaluation at Hang Nadim Malay School Middle School is conceptually relevant, however, in practice it has not been systematically coordinated, where teachers apply various evaluation models. While school facilities strongly support educational evaluation, this requires more holistic and comprehensive training on educational evaluation at SMP Hang Nadim Malay School Batam